Skuteczność sklerektomii głębokiej z implantacją Sk-gel i T-flux w 12-miesięcznej obserwacji - Rękas, Marek; Wierzbowska, Joanna; Lewczuk, Katarzyna; Siemiątkowska, Anna; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The purpose of this work was to present effectiveness and safety of phacodeepsclerectomy with SK-gel and T-flux implant in 12 months observation. Materials and methods: Retrospective analysis included group I (SK-gel) – 40 eyes and group II (T-flux) – 23 eyes. At the control studies best corrected visual acuity (BCVA), intraocular pressure (IOP), anterior and posterior segment of the eye were examined. Control testing was done in the first day and 7-th day, and 1, 3, 6, 12 months after surgery. In the case of elevated IOP (>15 mmHg) goniopuncture was performed. IOP (>15 mmHg) with fibrosis signs of the filtration bleb was an indication to use antimetabolites. Complete and qualified success rate was defined as IOP≤18 mmHg. In statistical analysis one-way ANOVA and Kaplan-Meier survival analysis, were used. Results: After 12 months mean IOP in the SK-gel group was 12.7 ± 0.6 mmHg and in T-flux group 14.6 ± 0.7 mmHg. It was a decrease in the mean IOP by 39.1% (p<.001) and 35.7% (p<.001). In both groups fewer medications were used than before surgery. Complete surgical and qualified success rate was reached in group I (81.7% and 91.9%) and in group II (72.7% and 83.8%). Nd:YAG goniopuncture performed in 10 eyes with implant SK-gel (25.0%) and 6 eyes with implant T-flux (26.1%) (p>.05). Subconjunctival injections with 5-FU were done in 5 eyes in the SK-gel group (12.5%) and in 3 eyes in the T-flux group (13.0%) (p>.05). Conclusions: Phacodeepsclerectomy (PDS) with SK-gel and T-flux implant are both effective and safe surgical methods in the treatment of POAG in 12 months observation.